Un lungo viaggio in una forma breve. Il videoclip musicale e il fenomeno della migrazione - Cristina Balma Tivola; Giuliana Galvagno (CoSMO, 2019)
The phenomenon of migration characterizes the contemporary world, giving rise to deep socio-economic and cultural changes. The music scene has been describing this situation for a long time, both denouncing publicly activities that harm human rights and supporting first-hand solidarity projects and initiatives through its influential and charismatic impact on millions of young people. Music videos – a hybrid kind of art between business and experimentation – take the form not only of a space for music visualization, but also for conveying a personal, political and social message. Those music videos that we analyse here address the issue of migration, showing  how it is being dealt with and articulated from time to time in representations that range from the real experiences of the artists themselves – raised among different cultures – to other more metaphorical and symbolic experiences through the use of diverse expressive forms, such as documentary, abstract, animated and archival images.